The need for the implementation of energy efficiency in the building of the northeast of Argentina (ARQUISUR Revista, 2018)
The natural growth of the population needs the concision of new buildings for different uses (housing, work, services, etc.) that should contemplate the problems of the XXIst century: the efficient use of the resources, like the energy, that makes the life and the development possible. The NEA–Region depends on the Electric power for the activities development in all the sectors, there still does not exist a distribution network of natural gas that could complement that of electric power. The high demand of electric power of the Building owes to the need to satisfy its basic habitability functions. In last 40 years an intensive urban development process took place, with growth edilicio quantitatively, not qualitatively. Argentina has occurred in a country dependent on the import to produce energy: from 2003 have been exported annual close to U$S 10 Billions to acquire Natural gas and Oil. 66 % of the generated electric power comes from fossil sources. 32 % has origin in nuclear and hydraulic. The offer of «clean energy» does not cover at present 2 % of the entire demand in Argentina and for 2050 it will reach only 10 % of the entire demand. The NEA would benefit with a politics of the regional state that encourages the buildings materialization energéticamente efficient.
Keywords: energy; technology; rules; sustainability; environment